UPAYA MILITER AZERBAIJAN DALAM MEMPERTAHANKAN PROVINSI NAGORNO KARABKH 2020 - Rahmatul Linsani; Sugeng Riyanto (Prodi Ilmu Hubungan Internasional, Universitas Fajar, 2023)
This paper refers to the phenomenon of conflict that occurred in 2020 in the Caucasus region. Where this conflict occurred between two countries, namely Azerbaijan and Armenia, which fought over a territory of Nagorno-Karabakh province. The war, which lasted for 40 days or approximately six weeks, was a concern for many parties. Every effort has been made to resolve this conflict both negotiation and mediation. This research uses qualitative methods that will make literature studies in helping to provide maximum results in this research. This research focuses more on Azerbaijan's reasons why it prefers to take on the policy of confrontation in the resolution of the 2020 conflict. Using John Lovel's strategy, the policy adopted by Azerbaijan is the right strategy taking into account its capabilities and the strategy of the opposing country. This research is expected to help international relations studies in providing references and becoming reference material in research in the same region.